2008
DOI: 10.1021/jp710997q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noncovalent Interactions on Conformers of the n-Butylbenzene Monomer Studied by Mass Analyzed Threshold Ionization Spectroscopy and Basis-set Convergent ab initio Computations

Abstract: Two conformational isomers of the aromatic hydrocarbon n-butylbenzene have been studied using two-color MATI (mass analyzed threshold ionization) spectroscopy to explore the effect of conformation on ionization dynamics. Cationic states of g auche-conformer III and anti- conformers IV were selectively produced by two-color excitation via the respective S 1 origins. Adiabatic ionization potentials of the gauche- and anti-conformations were determined to be 70146 and 69872 +/- 5 cm (-1) respectively. Spectral fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These methods can provide information about the active vibrations of rotamers in the electronically excited state. If the zero-kinetic energy (ZEKE) photoelectron [16][17][18] or mass-analyzed threshold ionization (MATI) [19][20][21][22][23] method couples with the resonant excitation scheme, it can provide information about the precise adiabatic IEs and active cation vibrations of the selected rotamers. Particularly, the MATI method has mass information and is suitable for studies of radicals, complexes, clusters, and isotopologues.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can provide information about the active vibrations of rotamers in the electronically excited state. If the zero-kinetic energy (ZEKE) photoelectron [16][17][18] or mass-analyzed threshold ionization (MATI) [19][20][21][22][23] method couples with the resonant excitation scheme, it can provide information about the precise adiabatic IEs and active cation vibrations of the selected rotamers. Particularly, the MATI method has mass information and is suitable for studies of radicals, complexes, clusters, and isotopologues.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution REMPI spectra and simulation based on MP2/cc-pVDZ computed rotational constants 20 allow to confirm the assignment of band A to conformer III and band D to conformer I (note that the conformer denomination in refs. [18][19][20][21] is different from that originally used by Simons and coworkers in refs. 15 and 16 ).…”
Section: Comparison With Experimental Datamentioning
confidence: 84%
“…Weaker transitions are attributed to conformer IV but no signal seems to correspond to conformer V. Owing to signal intensities, it is suggested that the relative population of conformers I-IV would be equal to 20/2.5/2.5/1. Conformers of butylbenzene have been also studied using resonance enhanced multiphoton ionization (REMPI), mass analyzed threshold ionization (MATI) and zero electron kinetic energy (ZEKE) spectroscopy 18,19,21 completed by quantum chemistry computations. 20,21 In their first experimental studies, Müller-Dethlefs and coworkers 18,19 examined the two colors REMPI spectrum of butylbenzene and found it clearly comparable to the LIF spectrum reported by Simons and coworkers 15 in 1997.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of knowledge, neither the ionization energy (IE) nor the cation spectrum of trans-2-fluorostyrene has been reported. Both zero-kinetic energy (ZEKE) photoelectron [6][7][8] and mass-analyzed threshold ionization (MATI) [9][10][11][12] spectroscopy are powerful methods for recording the vibrationally resolved cation spectra. These experimental results give information about the precise adiabatic IE and active molecular vibrations in the cationic ground D 0 state.…”
Section: Introductionmentioning
confidence: 99%